A Reading of 2 Kings 18:17–19:9a, 36–37 as a Trauma Narrative - Lee, Woo Min (2024)
The narrative of 2 Kings 18:17–19:9a, 36–37 (“Source B1”) recounts pre-exilic religious collective trauma surrounding Sennacherib’s military advance against Judah in 710 BCE and its aftermath. In this narrative, the Rabshakeh uses the keywords “בטח” and “נצל” to assert that Yhwh has turned against Judah. However, his claims were subverted by the withdrawal of the Assyrian army and the later death of Sennacherib, facilitated by the divine intervention of Yhwh following Hezekiah’s supplication. Despite its significance, only a few studies have examined this narrative as that of trauma. Drawing on Jeffrey Alexander’s theory of the social process of cultural or collective trauma, this study argues that the function of this narrative is that of religious trauma narrative. It reconstructs the collective trauma of Sennacherib’s campaign to theologically defend the Davidic kingship and Yhwh and ultimately suggests a revised identity for the Judaean community to foster solidarity, even under the ongoing influence of Assyria following the military campaign.
Keywords: Solidarity; identity revision; Hezekiah; the Rabshakeh; Sennacherib; trauma narrative; Collective Memory